Kajian Penanganan Gerusan pada Sungai Ciujung melalui Pemodelan Numerik : Study of Scour Treatment in the Ciujung River through Numerical Modeling - Putriasri, Anggun Etika; Hermawan, Yandi; Amatullah, Salma Izzatu; Rahmawati, Adhisye; Sandi, Calvin (Jurnal Teknik Sumber Daya Air, 2023)
The Ciujung River is known to have a meander river morphology, which has many bends. This causes several points in the river to be prone to erosion. In January 2023, the banks of the Ciujung River located in Bojong Catang Village experienced a landslide due to erosion which caused damage to several residents’ houses and threatened the surrounding settlements. Therefore, a treatment is needed to prevent erosion. Crib is a river structure that has a functions to regulate the direction of flow at river bends while protecting river banks against erosion. This study will test several alternative crib designs on the riverbanks of Bojong Catang Village. The simulation in this study was carried out using a 25-year return period flood discharge with a peak discharge of 1538,10 m3/s. Tests were carried out using numerical modeling with the aid of HEC-RAS 6.2 software to determine the flow speed at the outer bend of the river. The main objective of this study is to test the effectiveness of several design alternatives, as well as to provide crib design recommendations. From the results of modeling and analysis, it was found that to reduce the potential for landslides on river banks, with a length of ± 670 m in Bojong Catang Village, Alternative III groin design is recommended, with 12 impermeable crib, crib length of 31,85 meters, and the distance between each cribs is 57,33 meters. This alternative offers the most economical costs, with a smaller number of groins yet still has high effectiveness in reducing flow velocity at the outer bends of the river.